QUALITATIVE EVALUATION OF THE PSYCHOLOGICAL IMPLICATIONS OF CULTURE SHOCK ON NIGERIAN STUDENTS’ FIRST THREE MONTHS OF ACCULTURATION IN THE UNITED KINGDOM - EZE, Ogbonnia Eze; OSELEBE, Chisom Cherish; IGWE, Prince Benedict (EBSU Journal of Social Sciences and Humanities, 2024)
The exponential growth in Nigerian students’ migration to the United Kingdom has given scholars reasons to explore the kind of migration and acculturation experiences they have while pursuing their overseas education. This qualitative research aimed at exposing culture shock and acculturation problems and the psychological implications of these experiences in the lives of Nigerian students in UK universities. 50 participants (10 from each university) were conveniently selected from five universities in the United Kingdom. The universities included the following; Anglia Ruskin University, Cambridge University, Loughborough University, University of Lancaster and University of Bedfordshire. They were sampled using convenience and purposive sampling technique. The study was designed as a narrative inquiry and data was collected through telephone interviews. Narrative analysis was conducted and member checking was used to ensure that authentic information was analyzed. Findings revealed that the Nigerian students felt like a fish out of the water in the first three months of their migration to the United Kingdom. The result from the narrative analysis further indicated that the participants experienced psychological discomfort, a near feeling of depression, anxiety and a feeling of impotency all of which were attributed to culture shock. These findings imply that having appropriate and adequate information about a proposed host culture was important to help cushion the overwhelming effects of culture shock which are sometimes inevitable for sojourners abroad.